Integrasi Nilai-Nilai Kearifan Lokal dalam Pembelajaran PAI di SDIT Al-Markaz Al Islamiyah Kota Lhokseumawe - Hayati, Cut Intan; Nurasiah, Nurasiah; Bahri, Saiful (Yayasan Putroe Ceudah Aceh, 2024)
Integrated Islamic Religion Education (PAI) learning with local wisdom values as an important strategy in increasing the relevance and meaning of learning for students. This case study was conducted at SDIT al-Markaz al-Islamiyah Lhokseumawe City with the purpose of analyzing the application of integration the local wisdom values ​​in PAI learning. This study used a qualitative research approach with observation, interview, and documentation techniques. The results of the study indicated that the integration of local wisdom values ​​in PAI learning had increased student engagement on learning strategies with local values which are close and inherent to students. The strategies that were used included aligning materials with local values ​​that are full of sharia, identifying local values ​​and implementing traditions in society, integrating local wisdom values ​​into the curriculum, including folk tales such as Hikayat Aceh and Hadihmaja, as well as oral speech that applies in Acehnese society such as Meurukon, Peurateb Aneuk, and Hiem (riddles) and student involvement in developing teaching materials. Thus, Islamic Religion Education at SDIT al-Markaz al-Islamiyah Lhokseumawe City can be more relevant, meaningful, and encourage students' interest in understanding and practicing Islamic values ​​in their daily live values